Fairness in the distribution of land ownership in Indonesia based on Islamic law perspective - Koko Komaruddin (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
The imbalance of land ownership and tenure, which results in several land cases, becomes the main problem in agrarian sector in Indonesia that needs quick handling. Although the government has issued some policies related to the agrarian sector, such cases have not been completely solved. The main cause of the imbalance of land ownership is not merely about substance or policy related to land, but also the fundamental concept, philosophy, and orientation of the policy. Regarding this matter, this article explains Islamic point of view about fairness in distribution of land ownership as an alternative solution. Methodologically, this research is normative juridical research which is not only descriptive, but also prescriptive with doctrinal approach. According to a research conducted, every policy related to land issued by the government should be based on the principles of public interest or social justice as well as security of life and property, which become part of the concept of maqashid al-syarî’ah. Thus, the government must play an active role in the mechanism for the distribution and revocation of property rights over the land. Additionally, to make a fair and equitable the distribution of land, the government is required to provide supports, such as intensification and extensification so that all people are able to receive, manage, and use land ownership rights.